Anchored p90 Ribosomal S6 Kinase 3 is Required for Cardiac Myocyte Hypertrophy - Li, Jinliang (2012)
RATIONALE: Cardiac myocyte hypertrophy is the main compensatory response to chronic stress on the heart. p90 Ribosomal S6 Kinase (RSK) family members are effectors for extracellular signal-regulated kinases that induce myocyte growth. Although increased RSK activity has been observed in stressed myocytes, the functions of individual RSK family members have remained poorly defined, despite being potential therapeutic targets for cardiac disease. OBJECTIVE: To demonstrate that type 3 RSK (RSK3) is required for cardiac myocyte hypertrophy. METHODS AND RESULTS: RSK3 contains a unique N-terminal domain that is not conserved in other RSK family members. We show that this domain mediates the regulated binding of RSK3 to the muscle A-kinase anchoring protein (mAKAP) scaffold, defining a novel kinase anchoring event. Disruption of both RSK3 expression using RNA interference and RSK3 anchoring using a competing mAKAP peptide inhibited the hypertrophy of cultured myocytes. In vivo, RSK3 gene deletion in the mouse attenuated the concentric myocyte hypertrophy induced by pressure overload and catecholamine infusion. CONCLUSIONS: Taken together, these data demonstrate that anchored RSK3 transduces signals that modulate pathologic myocyte growth. Targeting of signaling complexes that contain select kinase isoforms should provide an approach for the specific inhibition of cardiac myocyte hypertrophy and for the development of novel strategies for the prevention and treatment of heart failure.